2014
DOI: 10.1007/s11255-014-0867-y
|View full text |Cite
|
Sign up to set email alerts
|

IL2-IL21 gene cluster polymorphism is not associated with allograft function after kidney transplantation

Abstract: Background Cytokines are key mediators of the immune response after transplantation. The interleukin (IL)-2 cytokine family, which includes IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21, is of particular interest because of its importance in the allogenic response. The aim of this study was to examine the association between the rs6822844 gene polymorphism in the IL2-IL21 region and allograft function after kidney transplantation.MethodsThe study enrolled 270 Caucasian kidney allograft recipients (166 males and 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We observed associations between polymorphisms in genes implicated in the immune response and renal allograft function in our earlier studies [16,17,18]. The current study assessed the linkage between inflammation and accelerated ageing of the transplanted kidney.…”
Section: Discussionmentioning
confidence: 79%
“…We observed associations between polymorphisms in genes implicated in the immune response and renal allograft function in our earlier studies [16,17,18]. The current study assessed the linkage between inflammation and accelerated ageing of the transplanted kidney.…”
Section: Discussionmentioning
confidence: 79%
“…Donors: African American and White [ 30 ] [ 31 ] -174, a (C>G) IL-6 Pro-inflammation and apoptosis 77 controls and recipients African American [ 30 ] +874 (CA) IFN-γ Pro-inflammation and apoptosis 77 controls and recipients African American [ 30 ] FyB null genotype or FyB null alleles and polymorphism at position 535 DARC DARC binds to chemokines and reduces their level. Limitation of systemic inflammation 222 recipients African American [ 32 ] -511 (promoter region) and exon-5 IL-1β Pro-inflammation 136 controls and recipients Indian [ 20 ] IL12B 3′UTR IL-12p40 Stimulating IFN-γ production 253 recipients Caucasian [ 33 ] CCR2-V64I CCR5-Delta32 CCR2 CCR5 Receptors of chemokines, which play a role in infiltration and activation of macrophages 100 donor–recipient pairs Iranian [ 34 ] rs6822844 IL2-IL21 cluster Regulation of T cells and NK cell functions 270 recipients Caucasian [ 35 ...…”
Section: Resultsmentioning
confidence: 99%
“…However, this association between the donor’s TNF-α gene polymorphisms and the occurrence of DGF failed to be confirmed in a large cohort including 512 African American and White donors [ 31 ]. Besides TNF-α, other cytokines have been genetically studied in DGF susceptibility, including IL-2 [ 35 , 30 ], IL-12 [ 33 ], transforming growth factor-β [ 31 , 30 , 21 ] and IL-16 and IL-18 [ 36 ]. None of these studies found an association with DGF susceptibility ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%